Evaluation of three alternatives for the control of varroasis (Varroa destructor) in ecuadorian apiaries - Díaz-Monroy, Byron; Moyón-Moyón, Juan; Baquero-Tapia, María Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In Chimborazo, Ecuador, three treatments were evaluated for the control of Varroasis (Varroa destructor) in bees, T1: Formic Acid (at 85%), T2: Oxalic Acid (at 10% in sugar syrup), T3: Thymol (at 99% diluted in olive oil), and a control treatment (T0), with a completely randomized design and four replicas (hives) for each treatment, during 30 days of application of the treatments on Langstroth hives. An initial diagnostic study was carried out to determine the level of varroasis infestation and select the 16 hives with the same level of infestation, then the treatments were applied, so the formic acid was applied twice, once every 15 days with a sprayer, the acid oxalic was applied four times, one every 4 days in sugar solution, thymol was applied twice, once every 8 days with spray and diluted in olive oil. A better efficacy (95.1%) was determined in the control of varroasis with formic acid, without affecting the population of bees, both by the mode of selective action of the product in the reproductive and foretic phase of the varroas, as by its long period of action, in addition to its low cost (8.2 dollars/hive), so it is recommended to use this product for the control of Varroa destructor in Apis mellifera.